1991
DOI: 10.1161/01.str.22.10.1291
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic deafferentation after focal cerebral infarct in rats.

Abstract: Background and Purpose: For a better understanding of neuronal network disturbances after stroke, we investigated the changes in the cholinergic system after experimental focal infarct Methods: We quantitatively evaluated the highly sensitive acetylcholinesterase histochemistry and local glucose utilization 7 days after left middle cerebral artery occlusion in Wistar rats.Results: In all rats with occlusion, ihe ipsilateral frontal cortex and the nucleus basalis Meynert developed no infarct, whereas the subcor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 25 publications
(15 reference statements)
3
20
0
Order By: Relevance
“…Previous studies have shown that the levels of ACh in rat brain are markedly decreased following MCA occlusion [24], and the numbers of muscarinic receptors and AChE-positive fibers are markedly decreased in the chronic phase after MCA occlusion in rats [25,26]. These reports suggested that LCBF decrease in our study is triggered by a deficiency of cholinergic systems.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies have shown that the levels of ACh in rat brain are markedly decreased following MCA occlusion [24], and the numbers of muscarinic receptors and AChE-positive fibers are markedly decreased in the chronic phase after MCA occlusion in rats [25,26]. These reports suggested that LCBF decrease in our study is triggered by a deficiency of cholinergic systems.…”
Section: Discussionsupporting
confidence: 58%
“…In the MCA occlusion model, the cholinergic basal forebrain complex is not involved in the infarcted area, but the cholinergic fibers from the basal nucleus to the cortex are injured. 29 It was reported that the acetylcholinesterase-positive fiber density was significantly reduced in the cortex on the occluded side and the acetylcholine levels in the infarcted cortex were significantly decreased. 29 " 31 Based on the results cited above, the memory disturbance observed in this study is ascribed to the impairment of cerebral neocortex.…”
Section: Discussionmentioning
confidence: 98%
“…The blood supply to the hippocampus, recognized for its key role in spatial memory, is not derived from the MCA (Scremin, 1995). Spatial memory deficits after MCAO reported using the watermaze may be explained by denervation of the hippocampus due to damaged projections from infarcted cortex, thalamic atrophy, or denervated basal nucleus cholinergic fibers to the cortex (Fujie et al, 1990;Kataoka et al, 1991). Alternatively, neocortical sites, some of which lie within the MCA territory, are known to be involved in spatial learning and memory (Frankland and Bontempi, 2005).…”
Section: Introductionmentioning
confidence: 99%